Desires of a perfect lady - Alexander, Victoria (Avon, 2010)
A decade ago, Lady Olivia Rathbourne had expected to marry the Earl of Wyldewood, only to have happiness stolen from her. Now that the Earl has vowed to rescue her, will he finally flaunt society's conventions and do with her what he's always wanted?